PARADIGMA INNOVATIVE LEADERSHIP: HARMONI INOVASI DAN KEPEMIMPINAN PROF. DR. KH ASEP SAIFUDDIN CHALIM - Regilza Alveronicha Lauranta Oribela (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Prof. Dr. KH. Asep Saifuddin Chalim, M.A. is a multifaceted leader who is not only known as a scholar but also as an academic, politician, writer, and founder of the Amanatul Ummah Islamic Boarding School. The diversity of roles reflects great commitment and attention to education, the benefit of the people, and innovation-oriented leadership values. He is known as a charismatic figure who is inspirational, generous, and creates a positive footprint in leading. He is also known as a leader who not only provides direction but also provides concrete actions which indirectly become a role model for his followers.